Respuesta :

To find the inverse of a funciton, you must switch the “x” and the “y” variables. As you said B is not a choice, I will take that out.

In the work below, I will switch f(x) with y, it makes no difference in the equation. But you’ll have to switch back to f(x).

A.

y= 2x+1

Inverse:

x=2y+1

x-1=2y

(x-1)/2= y

y= (x-1)/2

A is not an inverse

C.

y=(x+1)/5

Inverse

x=(y+1)/5

5x=y+1

5x-1=y

y=5x-1

C. Is not an inverse

D.

y=3x+2

Inverse

x=3y+2

x-2=3y

(x/3)-(2/3)=y

y=(x/3)-(2/3)

f(x)=(x/3)-(2/3)

SO D is the answer

Option D is the answer, sorry I have H.W to complete, so no time to explain...

Thank you have a magnificent day ahead...

If possible brainliest please

ACCESS MORE